Antropocentričeskoe izmerenie stilâ: (na materiale rasskazov V.V. Nabokova) - Smirnova, Nadežda V. (Stylistyka, 2020)
The principle of anthropocentrism, being the basis of human cognitive activity, detects the subject’s central position in the fictional universum. Possessing verbal fixation the subjects of the fictional text, the Narrator and the Character, interacting with each other form a subjective narration model. The stages of the subject’s representation in the fictional text related to the lack of knowledge of communicators’ field in general, are formally reflected in the sequence of nominations. The classic narration based on the maximum connectivity of its component elements, should tend to such a type of organization of the co-referential nominations’ rows, which would let the narratee clearly identify the object throughout the text. The deviances in the co-referential nominations’ rows, which occur in the non-classic narration, provoke referential interpretation and lead to the increment of text entropy. Basing on Vladimir Nabokov’s stories, two types of egocentric introductions in the co-referential nominations’ rows have been detected, based on the narration manner. The first type is reflected within the context of third-person narration, when a deictic first-person pronoun introduces itself with the identical reference as a proper noun, an anaphor, a substantive expression, into the sequence of character’s nominations. The second type is reflected in the first-person narration, it is related to the introduction into the sequence of nominations of a character not involved in the communication, a deictic second-person pronoun. “Egocentric explosions” in the co-referential nominations’ rows represent one of the most effective stylistic devices of the non-traditional narrative formation. They lead to the narrative mode switching providing stereoscopic effect.